APPLICATION OF THE TOPSIS PROCEDURE FOR EVALUATION OF SOCIO-ECONOMIC DEVELOPMENT OF THE WEST POMERANIAN VOIVODESHIP DISTRICTS IN YEARS 2004-2017 - Oesterreich, Maciej; Perzyńska, Joanna; Barej-Kaczmarek, Emilia (Management and Administration Journal, 2020)
The article presents the problem of local socio-economic development. An illustration of theoretical considerations is an empirical study on evaluation of the West Pomeranian Voivodship districts' development since Poland's accession to the European Union.  In the research, a taxonomic measure of development was used to assess the level and rate of districts' development. The empirical study was carried out in four main stages: collection of initial characteristics, reduction of the initial set of diagnostic features (to ensure their highest diagnostic value), calculations of synthetic measures using the modified TOPSIS procedure and construction of rankings of districts on that basis, creation of typological groups of districts characterized by a similar level and the pace of development. The study showed the existence of large diversification of economic development of the surveyed districts. The highest level of socio-economic development in both: 2004 and 2017 was characteristic for the Kamieński district and the lowest level of development in 2004 was observed in the Wałecki district and in 2017 in the Gryficki district. The highest pace of changes in the level of socio-economic development between 2004 and 2017 was recorded for the  Białogardzki district, while the lowest for the  Świdwiński district.